Towards the Mainstreaming of an Approach to Include Social Benefits Within Road Appraisal : A Case Study from Uganda - Odoki, Jennaro B.; Ahmed, Farhad; Taylor, Gary; Okello, Sunday A. (World Bank, Washington, DC, 2014)
Developing countries dedicate a considerable share of total infrastructure investment to roads. The adoption in 2000 of the Millennium Development Goals and an increasing emphasis on justifying road investments in terms of their contribution to poverty reduction have directed considerable attention to low volume rural roads. Often the poorest of the poor live in remote rural areas and improved access to social and economic services is a key factor in raising their living standards. The traditional road appraisal frameworks do not fit well with this trend as they generally ignore the impact of social benefit and poverty reduction. Past attempts to overcome these problems have lacked consistency. Therefore, there is a need to develop a consistent framework to address the poverty and social benefit aspects in a systematic manner. A study into the identification and treatment of social benefits in road transport project appraisal was conducted in 2003-04. The study highlighted the problems of identification, separation, measurement, forecasting and valuation of social benefits within a cost-benefit approach framework. It recommended a flexible approach using the principles of multi-criteria analysis (MCA) that is capable of combining qualitative and quantitative data into a single analytical framework. One of the study outputs was a computerized software tool that can be used alone or within the framework of globally accepted appraisal models. Although such tools appear to be robust in methodological terms, there are fundamental operational problems, including the choice of the benefits costs indicators and their weights. The current study undertook field testing of the proposed social benefits model and the software tool to recommend the choice of indicators with their corresponding weights based on results from the field. In addition, the study aimed to improve the capability of the Highway Development and Management Model (HDM-4) and social benefits software tools in addressing road investment related social issues.